2006
DOI: 10.1016/j.otohns.2006.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Use of anteriorly based pericranial flap in frontal sinus obliteration

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Cancellous autograft has the disadvantage of poor structural support. The potential disadvantages of pericranial flap frontal sinus obliteration are the devascularization of the anterior table and the flap vascular compromise (14). In our expirience autogenous cancellous bone graft is considered to be the best grafting material.…”
Section: Disscussion and Conclusionmentioning
confidence: 99%
“…Cancellous autograft has the disadvantage of poor structural support. The potential disadvantages of pericranial flap frontal sinus obliteration are the devascularization of the anterior table and the flap vascular compromise (14). In our expirience autogenous cancellous bone graft is considered to be the best grafting material.…”
Section: Disscussion and Conclusionmentioning
confidence: 99%
“…Moshaver et al . showed that an anteriorly based pericranial flap is a good option for frontal sinus obliteration 37 . None of their patients experienced recurrence.…”
Section: Discussionmentioning
confidence: 94%
“…8 Autografts, particularly the vascularized flaps have been reported to be superior in preventing CSF leak and infection. [10][11][12][13] The reconstruction in several layers is preferable in the presence of a large defect. 16,17 The first layer must be placed as an intradural underlay of fat, muscle, fascia or dural substitute.…”
Section: Discussionmentioning
confidence: 99%